Reinventing primaquine for endemic malaria. - Baird, J (2012)
After sixty years of continuous use, primaquine remains the only therapy licensed for arresting transmission and relapse of malaria. The US Army developed primaquine for soldiers in a wartime crisis setting. Dosing strategies suited to that narrow population were adopted without modification or validation for the broader population of humans exposed to risk of malaria. The poor suitability of these strategies in populations exhibiting greater vulnerability to hemolytic toxicity among glucose-6-phosphate dehydrogenase deficient patients has not been addressed. Primaquine requires chemotherapeutic reinvention delivering less threatening doses by leveraging unexplored co-drug synergies.